Identify Entrepreneurial Opportunity by Mining Data from Social Media - Muhamad Shahbani Abu Bakar, Syahida Hassan, Azman Ta’a, Azman Yasin, Ang Jin Sheng, Safiah Suhaimi , Khoo Yin Yin (International Journal of Advanced Science and Technology, 2020)
Social media plays an important role in marketing specifically in digital marketing. Many entrepreneur and businesses start to promote their brand and items on the social media platform such as Instagram. The main objective of this study is to crawl data from Instagram and perform some simple analysis to get some entrepreneurial ideas. A system named Graduate Entrepreneur Opportunity Recognition System (GEORsys) is proposed in this study. Hashtags for custom words or sectors like agriculture, services, food and beverages (F&B), fashion, information, communication and technology (ICT) and logistics are used to crawl data from Instagram. Then, some simple visualizations are shown to conclude what keywords or hashtags are popular in Instagram.